ECONOMIC AND LEGAL ASPECTS OF THE ACTIVITY COMMITTEE (AUDITOR) IN THE ASSOCIATION OF CO-OWNERS OF MULTI-APARTMENT BUILDING - O.V Tarasevich; S.S. Yatsenko (Економіка та право, 2018)
The association of co-owners of multi-apartment building (of households) (ACMB) is some kind of organization, the aim of which is to ensure and provide personal and economic interests of its members in better way, other than it was in the Soviet economy. Having its own structure, meaning statutory bodies, regarding the principle of the state powers balance, the same principle is used in the households’ organization discussed. The association has its «legislator», or general assembly, the «government», or the executive body called the board. So the economic and legal features are being discussed in the article brought. The activity of ACMHs (association of co-owners of multi-apartment building) as an entity requires adequate control by its owners — members of ACMBs. To ensure the rights of the general assembly and a audit committee (auditor) is elected. The current legislation does not fully contain legal instruments that would ensure the effectiveness of the audit committee (auditor), leaving the right to establish that rules of organization and activities to the general assembly of condominiums. The activities of the Audit Committee (Auditor) as the statutory body of ACMHs which clearly contains economic and legal features (aspects). The economic aspects include: professionalism, work in a nonprofit enterprise, the sphere of realization of internal economic relations, overwhelming gratuity, interchangeability with the service of the auditor, auxiliary character to ensuring the efficiency of complex service of the objects. The legal aspects include: limiting the audit committee (auditor) to the limits and in the manner determined by the general assembly, the declarative nature of the current normative provision, the informative nature of the conclusions of the audit committee, the internal economic nature of the documents of the audit committee, that is, their inadmissibility as evidence in court, not, like the auditor’s conclusion. Among other things, it was suggested that the general assembly approves the Procedure of the Audit Commission, which would eliminate the shortcomings of the legislation specified in this article.